Analysis, processing and prognosis of faults in combustion engines (otto) through vibration: application of artificial immune systems (Research, Society and Development, 2021)
This work demonstrates the application of artificial immunological systems (AIS) of negative selection in prognosis and detection of failures in fuel mixtures. The motivation of this study is related to the maintenance of OTTO cycle combustion engines, whose property differs from the physicochemical analyses of specialized laboratories. This work was divided into distinct phases, which were the execution of the experiment considering a motorcycle engine; signal collection and database formation considering gas station fuel (500ml); the gas station fuel (500ml) with 100ml of gas station ethanol; the gas station fuel (500ml) with 200ml of gas station ethanol. The result found of the different signals, after the application of the AIS, successfully demonstrated the grouping and classification of the signals of the databases.